2016
DOI: 10.1186/s40035-016-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlations of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by progressive neuronal loss and degeneration of upper motor neuron (UMN) and lower motor neuron (LMN). The clinical presentations of ALS are heterogeneous and there is no single test or procedure to establish the diagnosis of ALS. Most cases are diagnosed based on symptoms, physical signs, progression, EMG, and tests to exclude the overlapping conditions. Familial ALS represents about 5 ~ 10 % of ALS cases, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 127 publications
(144 reference statements)
3
64
0
1
Order By: Relevance
“…Indeed, twin studies revealed that each of the major phenotypes associated with neurofibromatosis type 1 is affected by distinct modifiers (Easton et al, 1993), none of which have yet been identified. This feature, along with the natural history of this complex disease and the relatively small number of recurrent mutations has precluded identification of clear genotype-phenotype correlations (Li and Wu, 2016). Recent psychiatric analysis of neurofibromatosis type 1 patients revealed that the NF1 gene functions as a quantitative trait locus that is associated with autism spectrum disorders (ASD) (Morris et al, 2016).…”
Section: Ras and Human Diseasementioning
confidence: 99%
“…Indeed, twin studies revealed that each of the major phenotypes associated with neurofibromatosis type 1 is affected by distinct modifiers (Easton et al, 1993), none of which have yet been identified. This feature, along with the natural history of this complex disease and the relatively small number of recurrent mutations has precluded identification of clear genotype-phenotype correlations (Li and Wu, 2016). Recent psychiatric analysis of neurofibromatosis type 1 patients revealed that the NF1 gene functions as a quantitative trait locus that is associated with autism spectrum disorders (ASD) (Morris et al, 2016).…”
Section: Ras and Human Diseasementioning
confidence: 99%
“…Variations of more than 30 genes have been associated with sporadic ALS, but these variations have not been linked to specific environmental risk factors, though epigenetics is a new area that is ripe for investigation [18]. The alteration of gene expression through DNA methylation, histone modification, and non-coding RNA-associated gene silencing are all targets of environmental insults considered to induce and sustain epigenetic changes that might result in neurodegeneration.…”
Section: Gene-environment Interactions In Alsmentioning
confidence: 99%
“…4 Since 1993, when the superoxide dismutase 1 (SOD1) gene was found to be mutated in fALS patients, an increasing number of disease genes, designated ALS 1-22, have been reported. 5 In 2009, ALS11 was identified as a rare autosomal dominant form of ALS associated with heterozygous deleterious variants of FIG4 in North American patients. 6 FIG4 encodes a phosphoinositide 5-phosphatase regulating phosphatidylinositol-3,5-bisphosphate, an intracellular signaling lipid with a key role in endosomal vesicle trafficking.…”
Section: Introductionmentioning
confidence: 99%